Hilirisasi Produk Pertanian Lokal : Pelatihan Teknik Pascapanen dan Analisis Kelayakan Bisnis untuk Meningkatkan Pendapatan Keluarga Di Kabupaten Seran Bagian Timur - Muspida; La Ega; Meiske Wenno; Muhammad Faisal; Erfendi Regar (PT. Penerbit Riset Sadwa, 2026)
This community service activity aimed to improve community knowledge and skills in managing local agricultural products through post-harvest technique training and business feasibility analysis in East Seram Regency. The main problems faced by the community were limited skills in agricultural product processing and lack of understanding of business management, causing local commodities such as sago, cassava, and coconut to be sold mostly in raw form with low economic value. The implementation methods included counseling, training, direct practice, and evaluation involving 25 participants consisting of farmers, housewives, and small business actors. The training materials covered post-harvest handling, product processing, packaging, and simple business feasibility analysis. The results showed an improvement in participants’ understanding and skills in processing local agricultural products into value-added products, as well as increased motivation to develop local resource-based businesses. This activity contributed positively to improving household income and strengthening sustainable community economic development in East Seram Regency.